2019
DOI: 10.12659/ajcr.918040
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Non-Operative Management of Atraumatic Splenic Hemorrhage Due to Snakebite Venom-Induced Consumption Coagulopathy

Abstract: Patient: Male, 62Final Diagnosis: Splenic hemorrhageSymptoms: Hypotension • syncopeMedication: —Clinical Procedure: Splenic artery angio-embolizationSpecialty: Critical Care MedicineObjective:Rare diseaseBackground:Snakebite envenoming results from injection of a mixture different toxins following snakebite. Coagulopathy and life-threatening hemorrhage can occur, or venom-induced consumption coagulopathy (VICC). A rare case is presented of spontaneous splenic hemorrhage due to VICC that was successfully treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…Similarly, a total of four cases of splenic rupture following bites from unidentified snake species one to five days after receiving antivenom were reported from South Korea (Kang et al, 2014;Kim et al, 2021;Lee and Sung, 2019;Yhi et al, 2013). Among these cases, three underwent splenectomy (Kang et al, 2014;Kim et al, 2021;Yhi et al, 2013) and in one case, it was averted by successful angioembolisation of splenic artery (Lee and Sung, 2019). To our knowledge, splenic rupture and subsequent splenectomy in Russell's viper bite victims has not been previously reported.…”
Section: Case Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Similarly, a total of four cases of splenic rupture following bites from unidentified snake species one to five days after receiving antivenom were reported from South Korea (Kang et al, 2014;Kim et al, 2021;Lee and Sung, 2019;Yhi et al, 2013). Among these cases, three underwent splenectomy (Kang et al, 2014;Kim et al, 2021;Yhi et al, 2013) and in one case, it was averted by successful angioembolisation of splenic artery (Lee and Sung, 2019). To our knowledge, splenic rupture and subsequent splenectomy in Russell's viper bite victims has not been previously reported.…”
Section: Case Discussionmentioning
confidence: 91%
“…Prior to this study, a cobra bite-induced splenic congestion was observed in a victim in 19 th century (as reviewed in (Feola et al, 2020)). Similarly, a total of four cases of splenic rupture following bites from unidentified snake species one to five days after receiving antivenom were reported from South Korea (Kang et al, 2014;Kim et al, 2021;Lee and Sung, 2019;Yhi et al, 2013). Among these cases, three underwent splenectomy (Kang et al, 2014;Kim et al, 2021;Yhi et al, 2013) and in one case, it was averted by successful angioembolisation of splenic artery (Lee and Sung, 2019).…”
Section: Case Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemoperitoneum as a consequence of VICC is a relatively rare complication. Non-traumatic splenic rupture and bleeding after snakebite has been described so far in three cases, of which only in one case initially intact spleen with massive hemoperitoneum and splenectomy necessity, has occurred (Kang et al, 2014;Lal et al, 2014;Lee and Sung, 2019).…”
Section: Introductionmentioning
confidence: 99%